Effect of high temperatures on the physical and mechanical properties of HDPE geomembranes in air. Issue 3 (1st March 2015) - Abdelaal, F. B.; Hsuan, Y. G.; Rowe, R. K.; Awad, R.
Abstract : ABSTRACT: The effect of elevated temperatures, particularly between 95 and 115°C as encountered in some geoenvironmental applications, on the physical and mechanical properties of high-density polyethylene (HDPE) geomembranes (GMBs) is examined. Four commercially available HDPE GMBs were incubated in air at temperatures ≥ 85°C. Investigation of the thermograms by differential scanning calorimetry showed a significant change in the polymer morphology with an increase of the incubation temperature and duration, especially at 105 and 115°C. The morphological changes due to annealing involve thickening of the lamella crystals of the polymer and a change in the tie molecules joining the lamella crystals. The effect of annealing was most evident in the stress crack resistance of the GMB incubated at 105 and 115°C prior to polymer degradation. In particular, an increase in stress crack resistance due to annealing could mask the effects of polymer degradation at temperatures above 95°C. Changes in morphology did not affect melt index whose changes were largely attributed to polymer degradation.